Influence of phase transitions on the temperature behavior of photoluminescence spectra in a (N(CH3)4)2MnCl4 crystal - Ilchuk, Hryhorii; Kashuba, Andrii; Kuno, Ivan; Sveleba, Sergey; Malyi, Taras; Petrus, Roman; Tsiumra, Volodymyr; Semkiv, Ihor (Eastern-European Journal of Enterprise Technologies, 2020)
Monocrystals (N(CH3)4)2MnCl4 were grown from an aqueous solution of salts by slow evaporation at room temperature. The effect of phase transitions on the behavior of photoluminescence spectra, as well as excitation spectra and time of attenuation of the glow band of 539 nm is studied in the temperature range of 4.5‒300 K. Based on the studies of the spectra of photoluminescence of the (N(CH3)4)2MnCl4, the glow bands, which are caused by the glow of the Mn2+ ion and correspond to the 4Т1→6А1 transition, were determined. The temperature evolution of photoluminescence spectra (4.5–300 K) of the (N(CH3)4)2MnCl4 crystal demonstrates anomalies of their parameters at the points of phase transitions. Temperature dependences of crystal photoluminescence spectra of the (N(CH3)4)2MnCl4 crystal prove the existence of phase transitions in the temperature intervals from 100 to 300 K. The excitation spectra for the luminescence band of 539 nm and their temperature evolution (4.5–300 K) are shown. The bands of around 2.93 and 2.96 eV are quickly damped with temperature, so at the temperatures above 170 K and 270 K, the bands of 2.96 and 2.93 eV are not observed, respectively. Peaks in the excitation spectrum correspond to electron transitions from the basic state of 6A1 Mn2+ to various excited states (Td). Their excitation energies are explained by a model of crystals using the Tanabe-Sugano diagrams. The Racah B and C parameters, as well as the splitting of crystal field Δ, were calculated based on the Tanabe-Sugano diagrams for d5 of electronic configuration. The temperature behavior of the time of attenuation of the photoluminescence band of 539 µm was studied. The resulting time of attenuation of the photoluminescence band increases at an increase in temperature. The kinetics of attenuation of the photoluminescence band of 539 µm of a crystal is well described by an exponential function